Local Self-Government in the Kingdom of Serbs, Croats and Slovenes - Drakić, Gordana; Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2018)
Abstract: Different views on the form of state organization emerged during the session of the Constituent Assembly in the newly formed Yugoslav state. This caused the formation of two political blocs in the Constituent Assembly centralist and federalist. Centralist bloc was formed of political parties that represented the majority in the Constituent Assembly. On the other side, federalist opposition bloc was consisted mostly of Croatian and Slovenian political parties. Various constitutional drafts that were submitted to the Constituent Committee comprised different possible solutions that were concerning local self-government. A system of particularly broad local self-government proposed a draft constitution that was prepared by Stojan Protić first Prime Minister in the Kingdom of Serbs, Croats and Slovenes. The Constitution of the Kingdom of Serbs, Croats and Slovenes adopted on 28 June 1921 proclaimed unitary state. According to the Constitution, the state territory had to be organized administratively into areas, districts and municipalities. Constitution had also set the framework for further legislative activity regarding the self-government issue in the Yugoslav state. The Law regarding local self-government was adopted in April 1922. Local self-government bodies were: district assembly and district committee. The scope of work of self-governing bodies was rather wide. The provisions of Law prescribed rather strong supervision over the functioning of the local self-government by the state authorities. Next step according to the provisions of the Law was to hold local elections in order to form local self-government bodies. However, the solutions adopted in the abovementioned law provoked disapproval of political circles in the state that had advocated federal state system. Tha,t combined with constant political instability, caused postponing of the aforementioned local elections until January 1927. After the local elections were held, it became clear that the legislation on local self-government had to be amended in order to organize local self-government on solid basis. Finally the local self-government was abolished during the Dictatorship of King Alexander Karađorđević.